Rubber composition for base part

The rubber composition for solid tires, featuring a diene-based rubber component, microfibers with a wide fiber diameter distribution, and large particle diameter carbon black, addresses the limitations of existing compositions by enhancing cutting, heat resistance, and durability.

JP7655056B2Active Publication Date: 2025-04-02SUMITOMO RUBBER INDUSTRIES LTD
View PDF 10 Cites 0 Cited by

Patent Information

Application Number
JP2021069296
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2021-04-15
Publication Date
2025-04-02
Estimated Expiration
2041-04-15

AI Technical Summary

Technical Problem

Existing rubber compositions for solid tires lack adequate cutting and heat resistance, which are critical for industrial vehicles operating under high loads and rough conditions.

Method used

A rubber composition for the base portion of solid tires, comprising a diene-based rubber component with isoprene-based rubber, butadiene-based rubber, and styrene-butadiene rubber, combined with microfibers having a wide fiber diameter distribution and carbon black with an average particle diameter of 30 nm or more.

Benefits of technology

The proposed rubber composition significantly enhances the overall performance of solid tires in terms of cutting and heat resistance, while also improving durability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007655056000003
    Figure 0007655056000003
  • Figure 0007655056000004
    Figure 0007655056000004
  • Figure 0007655056000005
    Figure 0007655056000005
Patent Text Reader

Abstract

To provide a rubber composition for a base part improved in cut resistance, and a solid tire using the rubber composition in a base part.SOLUTION: The rubber composition for a base part contains a diene rubber component, microfibers, and carbon black having an average particle diameter of 30 nm or more. The diene rubber component contains an isoprene rubber, a butadiene rubber and a styrene-butadiene rubber. The ratio of the maximum value to the minimum value of fiber diameters of the microfibers is 1.2 or more.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a rubber composition for a base portion and a solid tire using the rubber composition for a base portion. [Background technology]

[0002] Solid tires such as truck tires are used as tires for industrial vehicles such as forklifts. Industrial vehicles are used at relatively low speeds and with high loads on rough roads, so they are required to have various properties such as cut resistance and abrasion resistance.

[0003] Patent Document 1 describes a trash tire that uses a high hardness rubber composition in the base and has excellent fracture properties. [Prior art documents] [Patent documents]

[0004] [Patent Document 1] Japanese Patent Application Publication No. 7-118444 Summary of the Invention [Problem to be solved by the invention]

[0005] An object of the present invention is to provide a rubber composition for a base part which has improved overall performance in terms of cut resistance and heat resistance, and a solid tire using the rubber composition for the base part. [Means for solving the problem]

[0006] As a result of intensive research, the present inventors have found that the above-mentioned problems can be solved by a rubber composition containing a specific diene-based rubber component, microfibers having a wide fiber diameter distribution, and large particle size carbon black, and have completed the present invention.

[0007] That is, the present invention provides [1] A rubber composition for a base portion, comprising a diene rubber component, microfibers, and carbon black having an average particle diameter of 30 nm or more, wherein the diene rubber component comprises an isoprene rubber, a butadiene rubber, and a styrene-butadiene rubber, and the ratio of the maximum fiber diameter to the minimum fiber diameter of the microfibers is 1.2 or more; [2] The rubber composition according to [1] above, wherein the diene rubber component contains 70% by mass or more of an isoprene rubber. [3] The rubber composition according to [1] or [2] above, containing 40 parts by mass or more of carbon black having an average particle size of 40 nm or more per 100 parts by mass of the diene rubber component. [4] The rubber composition according to any one of the above [1] to [3], wherein the microfibers have an average fiber diameter of 0.1 to 100 μm. [5] The rubber composition according to any one of the above [1] to [4], containing 1 to 100 parts by mass of the microfibers per 100 parts by mass of the diene rubber component. [6] The rubber composition according to any one of the above [1] to [5], containing 0.1 to 20 parts by mass of a resin component per 100 parts by mass of the diene rubber component. [7] A solid tire using the rubber composition according to any one of [1] to [6] as a base part. [8] The solid tire according to [7] above, further comprising two or more cord layers in the base portion, the cord layers having at least one gap in a region near the tire equatorial plane in a tire posture before being mounted on an applicable rim. [9] The solid tire according to the above [7] or [8], wherein the ratio of the maximum width of the cord layer in the tire width direction to the rim width is 0.2 to 0.8, the ratio of the maximum height in the tire radial direction from the rim diameter line to the tire section height is 0.05 to 0.60, and the ratio of the minimum height in the tire radial direction from the rim diameter line to the tire section height is 0.01 to 0.50.

[10] The solid tire according to any one of [7] to [9] above, wherein the minimum width in the tire width direction of the gap portion is 1 mm or more and 70% or less of the maximum width in the tire width direction of the cord layer.

[11] The solid tire according to any one of the above [7] to

[10] , wherein a ratio of a maximum width in the tire width direction of an area in which the cords of the cord layer are arranged to a maximum width in the tire width direction of the cord layer is 0.2 to 0.8. Effect of the Invention

[0008] According to the present invention, there are provided a rubber composition for a base part, which has improved overall performance in terms of cut resistance and heat resistance, and a solid tire using the rubber composition for a base part. In a preferred embodiment, the durability of the solid tire is also improved. [Brief description of the drawings]

[0009] [Figure 1] 1 is a tire meridian cross-sectional view showing one embodiment of a solid tire of the present disclosure in a tire attitude before being mounted on an applicable rim. [Diagram 2] FIG. 4 is a tire meridian cross-sectional view showing another embodiment of a solid tire in a tire attitude before being mounted on an applicable rim. [Diagram 3] FIG. 1 is a schematic diagram showing a test device used to evaluate the cut resistance performance of a rubber composition in the present disclosure. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0010] The rubber composition for the base part according to the present disclosure contains a diene rubber component including isoprene rubber, butadiene rubber, and styrene butadiene rubber, microfibers, and carbon black having an average particle size of 30 nm or more, and the diene rubber component has a ratio of the maximum fiber diameter of the microfiber to the minimum fiber diameter of 1.2 or more. Although not intending to be bound by theory, the mechanism by which the effect of the present disclosure is exerted is thought to be, for example, as follows.

[0011] When a single rubber phase contains microfibers with large domains, there is a concern that cracks may occur at the boundary between the microfibers and the rubber phase. Therefore, by using a rubber component containing isoprene-based rubber, butadiene rubber, and styrene-butadiene rubber, and by using microfibers with a wide fiber diameter distribution, these components act cooperatively to form polymer domains of various sizes in the rubber component made of multiple components, which makes it difficult for cracks to occur, and even if cracks do occur, it is thought that there is a high probability that the cracks will stop at one of the interfaces.

[0012] In addition, by using carbon black with a large average particle size as a filler, it becomes easier to entangle with microfibers than carbon black with a small average particle size, and also interacts with the rubber component, so it is believed that cracks are less likely to occur and the strength of the rubber is improved compared to when only microfibers with low reinforcing properties are blended. On the other hand, it is believed that the heat generation of rubber can be reduced by using carbon black with a large average particle size.

[0013] As described above, it is believed that the combination of a specific rubber component, microfibers with a wide fiber diameter distribution, and large particle size carbon black achieves a remarkable effect of improving the overall performance of cut resistance and heat resistance.

[0014] The rubber composition for the base portion (hereinafter, sometimes simply referred to as the rubber composition) of the present disclosure preferably contains 70% by mass or more of an isoprene-based rubber in the diene-based rubber component.

[0015] The rubber composition preferably contains 40 parts by mass or more of carbon black having an average particle size of 40 nm or more per 100 parts by mass of the diene rubber component.

[0016] The average fiber diameter of the microfibers is preferably 0.1 to 100 μm.

[0017] The rubber composition preferably contains 1 to 100 parts by mass of the microfibers based on 100 parts by mass of the diene rubber component.

[0018] The rubber composition preferably contains 0.1 to 20 parts by mass of a resin component based on 100 parts by mass of the diene rubber component.

[0019] Another embodiment of the present disclosure is a solid tire using the above rubber composition in a base portion.

[0020] The solid tire of the present disclosure preferably includes two or more cord layers within the base portion, and the cord layers preferably have at least one gap in a region near the tire equatorial plane in the tire posture before being mounted on an applicable rim.

[0021] In the solid tire of the present disclosure, it is preferable that a ratio of a maximum width in the tire width direction of the cord layer to a rim width is 0.2 to 0.8, a ratio of a maximum height in the tire radial direction from the rim diameter line to a tire cross-sectional height is 0.05 to 0.60, and a ratio of a minimum height in the tire radial direction from the rim diameter line to a tire cross-sectional height is 0.01 to 0.50.

[0022] It is preferable that the maximum width of the gap in the tire width direction is 1 mm or more and 70% or less of the maximum width of the cord layer in the tire width direction.

[0023] In the solid tire of the present disclosure, it is preferable that a ratio of a maximum width in the tire width direction of a region in which the cords of the cord layer are arranged to a maximum width in the tire width direction of the cord layer is 0.2 to 0.8.

[0024] A solid tire including a rubber composition for a base part, which is one embodiment of the present disclosure, will be described in detail below. However, the following description is an example for explaining the present invention, and is not intended to limit the technical scope of the present invention to only this described range. In this specification, when a numerical range is indicated using "~", the numerical range is intended to include both ends of the range.

[0025] <Solid tires> FIG. 1 shows one embodiment of a solid tire according to the present disclosure, and is a meridian cross-sectional view of the tire in a tire attitude before being mounted on an applicable rim, although the present disclosure is not limited thereto.

[0026] The solid tire of the present disclosure includes an annular base portion 1 that is mounted on a rim, and a tread portion 2 that is provided radially outward of the base portion 1. The solid tire has a cord layer 3 that is provided annularly around the axis of rotation of the solid tire at a predetermined position from the inner circumferential surface of the base portion 1 toward the tread surface. A pair of cord layers 3 are provided spaced apart in the tire width direction across the tire equatorial plane CL, and a gap portion 4 formed by the rubber material of the base portion 1 is provided between the pair of cord layers 3 that are spaced apart in the tire width direction.

[0027] In the solid tire of the present disclosure, by providing at least one gap 4 in a region of the cord layer 3 near the tire equatorial plane in the tire posture before mounting on an applicable rim, bending of the cord due to compression in the width direction during vulcanization can be reduced, and the rubber in the gap can absorb bending deformation, reducing buckling of the cord layer 3. As a result, tire durability and rim slip resistance can be improved. Here, "near the tire equatorial plane CL" refers to a range of ±10% of the rim width D centered on the tire equatorial plane CL.

[0028] The cords in the cord layer 3 may be organic fiber cords in addition to steel cords.

[0029] The ratio (Bd / D) of the maximum width Bd in the tire width direction of the cord layer 3 to the rim width D is preferably 0.2 to 0.8, more preferably 0.4 to 0.8. The ratio (h1 / H) of the maximum height h1 in the tire radial direction from the rim diameter line to the tire cross-sectional height H is preferably 0.05 to 0.60, more preferably 0.05 to 0.45, and even more preferably 0.07 to 0.30. The ratio (h2 / H) of the minimum height h2 in the tire radial direction from the rim diameter line to the tire cross-sectional height H is preferably 0.01 to 0.50, more preferably 0.01 to 0.35, and even more preferably 0.02 to 0.20. With this configuration, the tire circumferential contact pressure distribution at the contact portion between the tire and the rim is made uniform, and the tire is maintained uniform during rolling under load, improving the frictional force with the rim, and as a result, the rim slip resistance can be improved. In this disclosure, the maximum height h1 in the tire radial direction refers to the distance measured from the rim diameter line to the radially outermost position of the cord layer 3 in a cross section in the tire width direction, and the minimum height h2 in the tire radial direction refers to the distance measured from the rim diameter line to the radially innermost position of the cord layer 3 in a cross section in the tire width direction.

[0030] The minimum width S of the gap 4 in the tire width direction is preferably 1 mm or more, more preferably 3 mm or more, even more preferably 5 mm or more, and particularly preferably 10 mm or more. The minimum width S of the gap 4 in the tire width direction is preferably 70% or less of the maximum width Bd of the cord layer 3 in the tire width direction, more preferably 60% or less, even more preferably 50% or less, and particularly preferably 40% or less. By setting the minimum width S of the gap 4 in the tire width direction in the above range, it is possible to achieve both the durability of the tire and the effect of rim slippage resistance. In this disclosure, the minimum width S of the gap 4 in the tire width direction means the minimum width of the gap between a pair of cord layers 3 spaced apart in the tire width direction.

[0031] The ratio of the maximum width in the tire width direction of the region where the cords of the cord layer 3 are arranged to the maximum width Bd of the cord layer 3 in the tire width direction is preferably 0.2 to 0.8, and more preferably 0.4 to 0.7. By setting it in the above range, the durability of the tire can be improved without reducing the rim slip resistance. In the present disclosure, the maximum width in the tire width direction of the region where the cords of the cord layer 3 are arranged is the length obtained by subtracting the minimum width S of the gap portion in the tire width direction from the maximum width Bd in the tire width direction, and in FIG. 1, it is the length represented by e1 + e2 on both sides of the tire equatorial plane.

[0032] The cords of the two cord layers 3 are inclined at an angle of 5° to 80° with respect to the circumferential direction of the tire, and the cords of each cord layer are intertwined with each other, thereby reducing the binding force of the cords against external inputs to the tire and further reducing rim slippage.

[0033] The solid tire of the present disclosure may be provided with a protrusion 5 that protrudes radially inwardly in the tire on one or both sides (one side in FIG. 2) below the rim diameter line of the base portion 1. Such a protrusion 5 has a structure that allows assembly without using a side ring used for rim assembly, thereby shortening the rim assembly time and reducing the rim costs.

[0034] <Rubber component> The rubber composition constituting the base part (rubber composition for base part) according to the present disclosure contains diene rubber including isoprene rubber, styrene butadiene rubber (SBR) and butadiene rubber (BR). The diene rubber may be a diene rubber component consisting of only isoprene rubber, styrene butadiene rubber (SBR) and butadiene rubber (BR).

[0035] (Isoprene rubber) As the isoprene-based rubber, for example, isoprene rubber (IR) and natural rubber, which are common in the tire industry, can be used. In addition to unmodified natural rubber (NR), natural rubber also includes modified natural rubber such as epoxidized natural rubber (ENR), hydrogenated natural rubber (HNR), deproteinized natural rubber (DPNR), highly purified natural rubber (UPNR), and grafted natural rubber. These isoprene-based rubbers may be used alone or in combination of two or more.

[0036] The NR is not particularly limited, and any NR commonly used in the tire industry can be used, such as SIR20, RSS#3, and TSR20.

[0037] From the viewpoint of cut resistance, the content of the isoprene rubber in the diene rubber component is preferably 70% by mass or more, more preferably 72% by mass or more, and even more preferably 75% by mass or more. The content is preferably 98% by mass or less, more preferably 94% by mass or less, even more preferably 90% by mass or less, and particularly preferably 86% by mass or less.

[0038] (BR) The BR is not particularly limited, and for example, one that is commonly used in the tire industry, such as BR having a cis content (amount of cis-1,4-bonded butadiene units) of 90 mol% or more (high cis BR), rare earth butadiene rubber synthesized using a rare earth catalyst (rare earth BR), BR containing syndiotactic polybutadiene crystals (SPB-containing BR), or modified BR (high cis modified BR, low cis modified BR), can be used.

[0039] Examples of high-cis BR include those manufactured by Zeon Corporation, Ube Industries, Ltd., and JSR Corporation. The inclusion of high-cis BR can improve low-temperature properties and wear resistance. The cis content of high-cis BR is preferably 90 mol% or more, more preferably 95 mol% or more, even more preferably 96 mol% or more, and particularly preferably 97 mol% or more. In the present disclosure, the cis content is a value calculated by infrared absorption spectrum analysis.

[0040] The rare earth BR is synthesized using a rare earth catalyst, and has a vinyl bond amount (amount of 1,2-bonded butadiene units) of preferably 1.8 mol% or less, more preferably 1.0 mol% or less, and even more preferably 0.8% or less, and a cis content (amount of cis-1,4-bonded butadiene units) of preferably 95 mol% or more, more preferably 96% or more, and even more preferably 97% or more. For example, a product manufactured by LANXESS LTD. can be used as the rare earth BR.

[0041] The SPB-containing BR is not one in which 1,2-syndiotactic polybutadiene crystals are simply dispersed in the BR, but one in which the 1,2-syndiotactic polybutadiene crystals are dispersed after being chemically bonded to the BR. Examples of such SPB-containing BR that can be used include those manufactured by Ube Industries, Ltd.

[0042] The modified BR preferably used is a terminal-modified BR coupled with tin, or a terminal-modified BR having an alkoxysilyl group and / or an amino group. The modified BR may be either non-hydrogenated or hydrogenated. The modified BR may be a product manufactured by Zeon Corporation or Asahi Kasei Chemicals Corporation.

[0043] The BRs listed above may be used alone or in combination of two or more.

[0044] The weight average molecular weight (Mw) of BR is preferably 300,000 or more, more preferably 350,000 or more, and even more preferably 400,000 or more, from the viewpoint of abrasion resistance and grip performance. From the viewpoint of crosslinking uniformity, it is preferably 2,000,000 or less, and more preferably 1,000,000 or less. Mw can be determined by standard polystyrene conversion based on the measured value obtained by gel permeation chromatography (GPC) (GPC-8000 series manufactured by Tosoh Corporation, detector: differential refractometer, column: TSKGEL SUPERMALTIPORE HZ-M manufactured by Tosoh Corporation).

[0045] From the viewpoint of cut resistance, the content of BR in the diene rubber component is preferably 1% by mass or more, more preferably 3% by mass or more, even more preferably 5% by mass or more, and particularly preferably 7% by mass or more. Also, the content is preferably 29% by mass or less, more preferably 27% by mass or less, even more preferably 25% by mass or less, even more preferably 22% by mass or less, even more preferably 20% by mass or less, and particularly preferably 18% by mass or less.

[0046] (SBR) There is no particular limitation on the SBR, and examples thereof include solution-polymerized SBR (S-SBR), emulsion-polymerized SBR (E-SBR), and modified SBRs thereof (modified S-SBR, modified E-SBR). Modified SBRs include SBRs whose ends and / or main chains are modified, and modified SBRs (condensates, those having a branched structure, etc.) coupled with tin, silicon compounds, etc. Among these, E-SBR is preferred from the viewpoint of being able to satisfactorily improve heat resistance and abrasion resistance. These SBRs may be used alone or in combination of two or more.

[0047] From the viewpoint of cut resistance, the content of SBR in the diene rubber component is preferably 1% by mass or more, more preferably 3% by mass or more, even more preferably 5% by mass or more, and particularly preferably 7% by mass or more. Also, the content is preferably 29% by mass or less, more preferably 27% by mass or less, even more preferably 25% by mass or less, even more preferably 22% by mass or less, even more preferably 20% by mass or less, and particularly preferably 18% by mass or less.

[0048] The diene rubber component according to the present disclosure may contain a diene rubber component other than the isoprene rubber, SBR, and BR. Examples of other diene rubber components include styrene isoprene butadiene rubber (SIBR), chloroprene rubber (CR), acrylonitrile butadiene rubber (NBR), etc. These other diene rubber components may be used alone or in combination of two or more.

[0049] <Microfiber> The rubber composition of the present disclosure contains microfibers. Such microfibers are not particularly limited, and any of natural fibers (plant fibers, animal fibers) and chemical fibers (synthetic fibers, semi-synthetic fibers, regenerated fibers) can be used. The above-mentioned microfibers may be used alone or in combination of two or more types.

[0050] Examples of synthetic fibers include polyethylene terephthalate (PET) fibers, polyethylene naphthalate fibers, polyester fibers, polyvinyl alcohol fibers, aramid fibers, nylon fibers, and rayon fibers, with PET fibers being preferred.

[0051] Examples of natural fibers include cellulose-based fibers, chitin-based fibers, and chitosan-based fibers.

[0052] The ratio of the maximum fiber diameter to the minimum fiber diameter of the microfibers is 1.2 or more, preferably 1.4 or more, more preferably 1.6 or more, even more preferably 1.7 or more, still more preferably 1.8 or more, and particularly preferably 1.9 or more. By using microfibers having such a wide fiber diameter distribution, it is believed that even if a crack occurs starting from the boundary between the microfiber and the rubber phase, the probability that the crack will stop at either interface is increased.

[0053] From the viewpoints of the rigidity and processability of the rubber composition, the average fiber diameter of the microfibers is preferably 0.1 μm or more, more preferably 0.5 μm or more, even more preferably 1.0 μm or more, even more preferably 5.0 μm or more, and particularly preferably 11 μm or more. From the viewpoints of the rigidity and breaking strength of the rubber composition, the average fiber diameter is preferably 100 μm or less, more preferably 80 μm or less, even more preferably 60 μm or less, and particularly preferably 45 μm or less.

[0054] The distribution of the fiber diameters of the fine fibers of the microfibers is determined by freeze-pulverizing a sample of the rubber composition, cutting the sample in a plane perpendicular to the extrusion direction of the rubber sheet, observing the cross section with a transmission electron microscope (TEM), and measuring the fiber diameters of, for example, 100 randomly selected microfibers, based on the measurement results. The minimum and maximum fiber diameters of the microfibers are determined as the maximum and minimum fiber diameters of the microfibers (for example, 100) observed with the TEM. The average fiber diameter of the microfibers is determined as the number average of the fiber diameters of the randomly selected microfibers.

[0055] The average fiber length of the microfibers is preferably 0.01 mm or more, more preferably 0.05 mm or more, even more preferably 0.10 mm, even more preferably 0.50 mm, and particularly preferably 1.0 mm. From the viewpoint of the rigidity and breaking strength of the rubber composition, the average fiber length of the microfibers is preferably 20 mm or less, more preferably 15 mm or less, even more preferably 10 mm or less, and particularly preferably 8.0 mm or less. In the present disclosure, the average fiber length of the microfibers can be measured by image analysis of scanning electron microscope photographs, image analysis of transmission microscope photographs, analysis of X-ray scattering data, pore electrical resistance method (Coulter principle method), etc.

[0056] The content of the microfibers per 100 parts by mass of the diene rubber component is preferably 1 part by mass or more, more preferably 3 parts by mass or more, even more preferably 5 parts by mass or more, and particularly preferably 7 parts by mass or more, from the viewpoint of cut resistance, and is preferably 100 parts by mass or less, more preferably 80 parts by mass or less, even more preferably 60 parts by mass or less, even more preferably 50 parts by mass or less, even more preferably 45 parts by mass or less, even more preferably 40 parts by mass or less, and particularly preferably 35 parts by mass or less, from the viewpoint of the breaking strength of the rubber composition.

[0057] <Carbon black> The rubber composition of the present disclosure contains carbon black having an average particle size of 30 nm or more. Examples of such carbon black include N550, N660, etc. These carbon blacks may be used alone or in combination of two or more.

[0058] The average particle size of carbon black is 30 nm or more, preferably 35 nm or more, more preferably 40 nm or more, and even more preferably 45 nm or more, from the viewpoint of easily entangling with microfibers and improving cut resistance. Also, the average particle size of carbon black is preferably 150 nm or less, more preferably 125 nm or less, and even more preferably 100 nm or less, from the viewpoint of weather resistance and reinforcing properties. In this specification, the average particle size of carbon black is a number average particle size, and is measured by a transmission electron microscope as the average value of 100 random particles.

[0059] The content of carbon black having an average particle size of 30 nm or more per 100 parts by mass of the rubber component is preferably 40 parts by mass or more, more preferably 42 parts by mass or more, even more preferably 45 parts by mass or more, and particularly preferably 47 parts by mass or more, from the viewpoint of cut resistance. Also, from the viewpoint of heat resistance, the content is preferably 100 parts by mass or less, more preferably 90 parts by mass or less, and even more preferably 80 parts by mass or less.

[0060] The rubber composition of the present disclosure may contain carbon black having an average particle diameter of less than 30 nm, but the amount thereof is preferably 20 parts by mass or less, more preferably 10 parts by mass or less, and even more preferably 1 part by mass or less, per 100 parts by mass of the rubber component. It is particularly preferable that the rubber composition does not contain carbon black having an average particle diameter of less than 30 nm.

[0061] As fillers other than carbon black, for example, silica, aluminum hydroxide, calcium carbonate, alumina, clay, talc, and the like, which are commonly used in the tire industry, can be used.

[0062] The silica is not particularly limited, and can be, for example, silica prepared by a dry method (anhydrous silica), silica prepared by a wet method (hydrated silica), or other silica commonly used in the tire industry. Among them, hydrated silica prepared by a wet method is preferred because it contains a large number of silanol groups. These silicas can be used alone or in combination of two or more.

[0063] The nitrogen adsorption specific surface area (N2SA) of silica is 110m from the viewpoint of fracture resistance and wear resistance. 2 / g or more is preferable, and 130m 2 / g or more is more preferable, and 150m 2 / g or more is more preferable, and 170m 2 From the viewpoint of heat resistance and processability, it is particularly preferable that the tensile strength is 350 m / g or more. 2 / g or less is preferable, and 300m 2 / g or less is more preferable, and 250m 2 / g or less is more preferable. In this specification, the N2SA of silica is a value measured by the BET method in accordance with ASTM D3037-93.

[0064] When silica is contained, the content per 100 parts by mass of the rubber component is preferably 30 parts by mass or less, more preferably 25 parts by mass or less, further preferably 20 parts by mass or less, and particularly preferably 15 parts by mass or less, from the viewpoint of cut resistance. On the other hand, the lower limit of the silica content is not particularly limited, and can be, for example, 1 part by mass or more, 3 parts by mass or more, or 5 parts by mass or more per 100 parts by mass of the rubber component, and silica may not be contained.

[0065] (Silane coupling agent) Silica is preferably used in combination with a silane coupling agent. The silane coupling agent is not particularly limited, but may be, for example, a sulfide-based silane coupling agent such as bis(3-triethoxysilylpropyl) disulfide or bis(3-triethoxysilylpropyl) tetrasulfide; a mercapto-based silane coupling agent such as 3-mercaptopropyltrimethoxysilane, NXT-Z100, NXT-Z45, or NXT manufactured by Momentive; a vinyl-based silane coupling agent such as vinyltriethoxysilane or vinyltrimethoxysilane; a 3-aminopropyltriethoxysilane or 3-aminopropyltrimethoxysilane; Examples of the silane coupling agents include amino-based silane coupling agents such as silane and 3-(2-aminoethyl)aminopropyltriethoxysilane; glycidoxy-based silane coupling agents such as γ-glycidoxypropyltriethoxysilane and γ-glycidoxypropyltrimethoxysilane; nitro-based silane coupling agents such as 3-nitropropyltrimethoxysilane and 3-nitropropyltriethoxysilane; chloro-based silane coupling agents such as 3-chloropropyltrimethoxysilane and 3-chloropropyltriethoxysilane, and sulfide-based silane coupling agents are preferred. These silane coupling agents may be used alone or in combination of two or more.

[0066] When containing silane coupling agent, the content relative to 100 parts by mass of silica is preferably 8.0 parts by mass or more, more preferably 8.5 parts by mass or more, even more preferably 9.0 parts by mass or more, and particularly preferably 9.5 parts by mass or more, from the viewpoint of improving the dispersibility of silica.In addition, from the viewpoint of preventing the deterioration of abrasion resistance, it is preferably 18 parts by mass or less, more preferably 16 parts by mass or less, even more preferably 14 parts by mass or less, and particularly preferably 12 parts by mass or less.

[0067] <Other compounding agents> In addition to the above-mentioned components, the rubber composition according to the present disclosure may appropriately contain compounding agents commonly used in the tire industry, such as oil, resin components, wax, processing aids, antioxidants, vulcanizing agents such as stearic acid, zinc oxide and sulfur, vulcanization accelerators, and the like.

[0068] Examples of the oil include process oil, vegetable oil, and animal oil. Examples of the process oil include paraffin-based process oil, naphthenic process oil, and aromatic process oil. In addition, as an environmental measure, process oil with a low content of polycyclic aromatic compound (PCA) compounds can be used. Examples of the low PCA content process oil include light extract solvate (MES), treated distillate aromatic extract (TDAE), and heavy naphthenic oil.

[0069] When oil is contained, the content per 100 parts by mass of the rubber component is preferably 1 part by mass or more, more preferably 5 parts by mass or more, and even more preferably 10 parts by mass or more from the viewpoint of processability. Also, from the viewpoint of abrasion resistance, the content is preferably 80 parts by mass or less, more preferably 70 parts by mass or less, and even more preferably 60 parts by mass or less. In this specification, the content of oil includes the amount of oil contained in the oil-extended rubber.

[0070] The resin component is not particularly limited, but examples thereof include petroleum resins, terpene resins, rosin resins, phenol resins, etc. These resin components may be used alone or in combination of two or more.

[0071] In this specification, the term "C5 petroleum resin" refers to a resin obtained by polymerizing a C5 fraction. Examples of C5 fractions include petroleum fractions having 4 to 5 carbon atoms, such as cyclopentadiene, pentene, pentadiene, and isoprene. As the C5 petroleum resin, dicyclopentadiene resin (DCPD resin) is preferably used.

[0072] In this specification, the term "aromatic petroleum resin" refers to a resin obtained by polymerizing a C9 fraction, and may be a hydrogenated or modified resin. Examples of the C9 fraction include petroleum fractions having 8 to 10 carbon atoms, such as vinyltoluene, alkylstyrene, indene, and methylindene. Specific examples of aromatic petroleum resins that are preferably used include coumarone-indene resins, coumarone resins, indene resins, and aromatic vinyl resins. As the aromatic vinyl resin, a homopolymer of α-methylstyrene or styrene or a copolymer of α-methylstyrene and styrene is preferred, and a copolymer of α-methylstyrene and styrene is more preferred, because they are economical, easy to process, and have excellent heat resistance. As the aromatic vinyl resin, for example, a commercially available product from Kraton, Eastman Chemical, etc. can be used.

[0073] In this specification, the term "C5C9 petroleum resin" refers to a resin obtained by copolymerizing the C5 fraction and the C9 fraction, and may be a hydrogenated or modified resin. Examples of the C5 fraction and the C9 fraction include the petroleum fractions described above. As the C5C9 petroleum resin, for example, those commercially available from Tosoh Corporation, LUHUA, etc. can be used.

[0074] Examples of the terpene resin include polyterpene resins consisting of at least one selected from terpene compounds such as α-pinene, β-pinene, limonene, and dipentene; aromatic modified terpene resins made from the terpene compounds and aromatic compounds; terpene phenolic resins made from terpene compounds and phenolic compounds; and terpene resins obtained by subjecting these terpene resins to hydrogenation treatment (hydrogenated terpene resins). Examples of aromatic compounds that are raw materials for aromatic modified terpene resins include styrene, α-methylstyrene, vinyltoluene, and divinyltoluene. Examples of phenolic compounds that are raw materials for terpene phenolic resins include phenol, bisphenol A, cresol, and xylenol.

[0075] The rosin-based resin is not particularly limited, but examples thereof include natural rosin resin and rosin-modified resins obtained by modifying rosin by hydrogenation, disproportionation, dimerization, esterification, or the like.

[0076] The phenol-based resin is not particularly limited, but examples thereof include phenol formaldehyde resin, alkylphenol formaldehyde resin, alkylphenol acetylene resin, and oil-modified phenol formaldehyde resin.

[0077] When a resin component is contained, the content per 100 parts by mass of the rubber component is preferably 1 part by mass or more, more preferably 3 parts by mass or more, and even more preferably 5 parts by mass or more from the viewpoint of wet grip performance, and is preferably 50 parts by mass or less, more preferably 40 parts by mass or less, even more preferably 30 parts by mass or less, and particularly preferably 20 parts by mass or less from the viewpoint of heat resistance.

[0078] When the wax is contained, the content thereof per 100 parts by mass of the rubber component is preferably 0.5 parts by mass or more, more preferably 1.0 parts by mass or more, and even more preferably 1.5 parts by mass or more from the viewpoint of weather resistance of the rubber, and is preferably 8.0 parts by mass or less, more preferably 6.0 parts by mass or less from the viewpoint of preventing whitening of the tire due to bloom.

[0079] Examples of the processing aid include fatty acid metal salts, fatty acid amides, amide esters, silica surfactants, fatty acid esters, mixtures of fatty acid metal salts and amide esters, mixtures of fatty acid metal salts and fatty acid amides, etc. These processing aids may be used alone or in combination of two or more. Examples of the processing aids that can be used include those commercially available from Schill+Seilacher, Performance Additives, etc.

[0080] When a processing aid is contained, the content thereof per 100 parts by mass of the rubber component is preferably 0.5 parts by mass or more, more preferably 1 part by mass or more, from the viewpoint of improving processability, and is preferably 10 parts by mass or less, more preferably 8 parts by mass or less, from the viewpoints of abrasion resistance and breaking strength.

[0081] The antiaging agent is not particularly limited, but examples thereof include amine-based, quinoline-based, quinone-based, phenol-based, and imidazole-based compounds, and carbamic acid metal salts, and the like. Phenylenediamine-based antiaging agents such as N-(1,3-dimethylbutyl)-N'-phenyl-p-phenylenediamine, N-isopropyl-N'-phenyl-p-phenylenediamine, N,N'-diphenyl-p-phenylenediamine, N,N'-di-2-naphthyl-p-phenylenediamine, and N-cyclohexyl-N'-phenyl-p-phenylenediamine, and quinoline-based antiaging agents such as 2,2,4-trimethyl-1,2-dihydroquinoline polymer and 6-ethoxy-2,2,4-trimethyl-1,2-dihydroquinoline are preferred. These antiaging agents may be used alone or in combination of two or more.

[0082] When an antioxidant is contained, the content per 100 parts by mass of the rubber component is preferably 0.5 parts by mass or more, more preferably 1.0 parts by mass or more, and even more preferably 1.5 parts by mass or more from the viewpoint of ozone crack resistance of the rubber, and is preferably 10.0 parts by mass or less, more preferably 5.0 parts by mass or less from the viewpoint of abrasion resistance and wet grip performance.

[0083] When stearic acid is contained, the content thereof per 100 parts by mass of the rubber component is preferably 0.5 parts by mass or more, more preferably 1 part by mass or more, from the viewpoint of processability, and is preferably 10 parts by mass or less, more preferably 5 parts by mass or less, from the viewpoint of vulcanization speed.

[0084] When zinc oxide is contained, the content per 100 parts by mass of the rubber component is preferably 0.5 parts by mass or more, more preferably 1.0 parts by mass or more, and even more preferably 1.5 parts by mass or more from the viewpoint of processability, and is preferably 10.0 parts by mass or less, more preferably 5.0 parts by mass or less from the viewpoint of abrasion resistance.

[0085] As the vulcanizing agent, sulfur is preferably used, and examples of the sulfur that can be used include powdered sulfur, oil-treated sulfur, precipitated sulfur, colloidal sulfur, insoluble sulfur, and highly dispersible sulfur.

[0086] When sulfur is used as a vulcanizing agent, the content of sulfur is preferably 0.5 parts by mass or more, more preferably 1.0 parts by mass or more, based on 100 parts by mass of the rubber component, from the viewpoint of ensuring sufficient vulcanization reaction and obtaining good grip performance and wear resistance. From the viewpoint of deterioration, the content is preferably 3.0 parts by mass or less, more preferably 2.5 parts by mass or less, and even more preferably 2.0 parts by mass or less. When oil-containing sulfur is used as a vulcanizing agent, the content of the vulcanizing agent is the total content of pure sulfur contained in the oil-containing sulfur.

[0087] Examples of vulcanizing agents other than sulfur include alkylphenol-sulfur chloride condensates, sodium 1,6-hexamethylene-dithiosulfate dihydrate, 1,6-bis(N,N'-dibenzylthiocarbamoyldithio)hexane, etc. As these vulcanizing agents other than sulfur, commercially available products from Taoka Chemical Co., Ltd., Lanxess Co., Ltd., Flexis, etc. can be used.

[0088] Examples of the vulcanization accelerator include sulfenamide-based, thiazole-based, thiuram-based, thiourea-based, guanidine-based, dithiocarbamic acid-based, aldehyde-amine-based or aldehyde-ammonia-based, imidazoline-based, and xanthate-based vulcanization accelerators. These vulcanization accelerators may be used alone or in combination of two or more. Among them, one or more vulcanization accelerators selected from the group consisting of sulfenamide-based, guanidine-based, and thiazole-based vulcanization accelerators are preferred.

[0089] Examples of sulfenamide vulcanization accelerators include N-tert-butyl-2-benzothiazolylsulfenamide (TBBS), N-cyclohexyl-2-benzothiazolylsulfenamide (CBS), N,N-dicyclohexyl-2-benzothiazolylsulfenamide (DCBS), etc. Among them, N-tert-butyl-2-benzothiazolylsulfenamide (TBBS) is preferred.

[0090] Examples of the guanidine vulcanization accelerator include 1,3-diphenylguanidine (DPG), 1,3-di-o-tolylguanidine, 1-o-tolylbiguanide, di-o-tolylguanidine salt of dicatechol borate, 1,3-di-o-cumenylguanidine, 1,3-di-o-biphenylguanidine, 1,3-di-o-cumenyl-2-propionylguanidine, etc. Among them, 1,3-diphenylguanidine (DPG) is preferable.

[0091] Examples of the thiazole-based vulcanization accelerator include 2-mercaptobenzothiazole, cyclohexylamine salt of 2-mercaptobenzothiazole, di-2-benzothiazolyl disulfide, etc. Among these, 2-mercaptobenzothiazole is preferred.

[0092] When a vulcanization accelerator is contained, the content per 100 parts by mass of the rubber component is preferably 1 part by mass or more, more preferably 2 parts by mass or more, and even more preferably 3 parts by mass or more. The content per 100 parts by mass of the rubber component is preferably 8 parts by mass or less, more preferably 7 parts by mass or less, and even more preferably 6 parts by mass or less. By setting the content of the vulcanization accelerator within the above range, breaking strength and elongation tend to be secured.

[0093] The rubber composition of the present disclosure can be produced by a known method, for example, by kneading the above-mentioned components using a rubber kneading device such as an open roll or an internal kneader (such as a Banbury mixer or kneader).

[0094] The kneading step includes, for example, a base kneading step in which compounding ingredients and additives other than the vulcanizing agent and the vulcanization accelerator are kneaded, and a final kneading (F kneading) step in which the vulcanizing agent and the vulcanization accelerator are added to the kneaded product obtained in the base kneading step and kneaded. Furthermore, the base kneading step can be divided into a plurality of steps as desired.

[0095] The kneading conditions are not particularly limited, but examples thereof include a method in which in the base kneading step, kneading is performed for 3 to 10 minutes at a discharge temperature of 150 to 170° C., and in the final kneading step, kneading is performed for 1 to 5 minutes at 70 to 110° C. The vulcanization conditions are not particularly limited, but examples thereof include a method in which vulcanization is performed for 10 to 30 minutes at 150 to 200° C.

[0096] A solid tire having a base part can be manufactured by a normal method using the above-mentioned rubber composition. That is, an unvulcanized rubber composition obtained by blending the above-mentioned components with a rubber component as necessary is extruded to match the shape of the base part using an extruder equipped with a die of a predetermined shape, and is laminated together with the tread part and other tire components on a tire building machine and molded by a normal method to form an unvulcanized tire, and the unvulcanized tire is heated and pressurized in a vulcanizer to manufacture the solid tire of the present disclosure. EXAMPLES

[0097] Hereinafter, the present disclosure will be described based on examples, but the present disclosure is not limited to these examples.

[0098] The various chemicals used in the examples and comparative examples are listed below. NR:TSR20 BR: UBEPOL BR150B manufactured by Ube Industries, Ltd. (cis content: 97 mol%, Mw: 440,000) SBR: SBR1502 manufactured by JSR Corporation (E-SBR, styrene content: 23.5% by mass, vinyl content: 18% by mole, Mw: 420,000) Carbon black 1: Diablack N550 (average particle size: 48 nm) manufactured by Mitsubishi Chemical Corporation Carbon black 2: Diablack N660 (average particle size: 80 nm) manufactured by Mitsubishi Chemical Corporation Carbon black 3: Diablack N220 (average particle size: 23 nm) manufactured by Mitsubishi Chemical Corporation Microfiber 1: PET fiber (average fiber diameter: 27 μm, ratio of maximum to minimum fiber diameter: 2.1, average fiber length: 5 mm) Microfiber 2: PET fiber (average fiber diameter: 35 μm, ratio of maximum to minimum fiber diameter: 1.8, average fiber length: 5 mm) Microfiber 3: PET fiber (average fiber diameter: 10 μm, ratio of maximum to minimum fiber diameter: 1.1, average fiber length: 5 mm) Silica: Ultrasil VN3 (N2SA: 175m) manufactured by Evonik Degussa 2 / g) Silane coupling agent: Si266 (bis(3-triethoxysilylpropyl) disulfide) manufactured by Evonik Degussa Resin component: YS Resin TO125 (terpene styrene resin) manufactured by Yasuhara Chemical Co., Ltd. Anti-aging agent: Nocrac 6C (N-(1,3-dimethylbutyl)-N'-phenyl-p-phenylenediamine) manufactured by Ouchi Shinko Chemical Industry Co., Ltd. Stearic acid: Beads of stearic acid camellia manufactured by NOF Corporation Zinc oxide: Zinc oxide No. 1 manufactured by Mitsui Mining & Smelting Co., Ltd. Sulfur: SEIMI OT (insoluble sulfur containing 10% oil) manufactured by Nippon Kanretsu Kogyo Co., Ltd. Vulcanization accelerator: Noccela NS (N-tert-butyl-2-benzothiazolyl sulfenamide (TBBS)) manufactured by Ouchi Shinko Chemical Industry Co., Ltd.

[0099] Examples and Comparative Examples According to the compounding recipe shown in Table 1, the chemicals other than sulfur and the vulcanization accelerator were kneaded for 5 minutes until the discharge temperature reached 170°C using a 1.7L closed Banbury mixer, and a kneaded product was obtained. Furthermore, the obtained kneaded product was kneaded again (remilled) for 4 minutes at a discharge temperature of 150°C using the Banbury mixer. Next, sulfur and the vulcanization accelerator were added to the obtained kneaded product using a two-axis open roll, and the mixture was kneaded for 4 minutes until the temperature reached 105°C, and an unvulcanized rubber composition was obtained. The obtained unvulcanized rubber composition was press-vulcanized at 170°C for 12 minutes to produce a vulcanized rubber composition. In addition, the unvulcanized rubber composition of Example 1 was extruded into the shape of a base part using an extruder equipped with a die of a predetermined shape, and was laminated together with a tread part and other tire components to form an unvulcanized tire, and press-vulcanized to produce a tread tire.

[0100] <Evaluation of cut resistance> The cut resistance of the obtained vulcanized rubber composition was evaluated using the test device described in JP 2019-113399 A. FIG. 3 shows the basic configuration of the test device 32.

[0101] A test piece 34 (length: 100 mm, width: 10 mm, thickness: 10 mm) was prepared from the obtained vulcanized rubber composition. The mass of the weight 84 was set to 30 kg. The length L of the arm 82 was set to 1.09 m. A double-edged blade (angle α=20°, thickness TB=2 mm, width (depth)=20 mm) was used as the blade 52.

[0102] Both ends of the test piece 34 were gripped by the gripping means 56 of the testing device, and the test piece was set in the fixing part 50 so that the first surface of the test piece was located on the blade side. The upper gripping means was moved toward the lower gripping means by the actuator 58, and the spacer 60 was pressed against the back surface 74 of the test piece, thereby bending the test piece 34. The radius of curvature of the arc representing the outline of the surface of the test piece in the curved state was 110 mm.

[0103] The weight 84 was lifted and released to strike the tip PT of the curved test piece with the blade. The initial angle θ between the arm when the weight was lifted and the arm when the weight was directly below was 36°.

[0104] Whether the blade reached the steel cord was judged by the sound of impact. If there was no sound when impacting and the blade had not reached the steel cord, the test piece was replaced with a new test piece, the angle θ was increased by 2°, and the test was performed on this new test piece. While increasing the angle θ in increments of 2°, the test piece was repeatedly struck by the blade until it reached the steel cord, and the angle θ at which the blade reached the steel cord was determined.

[0105] The potential energy was calculated from the obtained angle θ, the arm length LA, the mass of the weight, and the gravitational acceleration, and this was shown as the breaking energy (J). In addition, the breaking energy of Comparative Example 2 was set to 100, and an index was displayed according to the following formula. A larger index indicates better cut resistance. (Cut resistance performance index) = (Fracture energy of each compounding example) / (Fracture energy of Comparative Example 2)×100

[0106] <Evaluation of heat resistance performance> The obtained vulcanized rubber composition was made into a sheet-shaped vulcanized rubber test piece, and the loss tangent (tan δ) was measured at a temperature of 70°C, an initial strain of 5%, a dynamic strain of ±1%, and a frequency of 10 Hz using a viscoelasticity spectrometer RSA-G2 manufactured by TA Instruments in accordance with JIS K 6394:2007. The reciprocal value of tan δ at 70°C was expressed as an index (heat resistance performance index) with the value of Comparative Example 2 set at 100. A larger index indicates better heat resistance performance. (Heat resistance performance index)=(70° C. tan δ of the vulcanized rubber test piece of Comparative Example 2) / (70° C. tan δ of the vulcanized rubber test piece of each test tire)×100

[0107] The target performance value for the overall cut resistance and heat resistance (the sum of the cut resistance index and heat resistance index) is over 200.

[0108] [Table 1]

[0109] The results in Table 1 show that the rubber composition for the base part of the present disclosure, which contains a diene rubber component, microfibers with a wide fiber diameter distribution, and large particle size carbon black, has improved overall cut resistance and heat resistance.

[0110] <Durability evaluation> The durability of the above-mentioned truck tire using the rubber composition of Example 1 as the base was evaluated by the following method. The dimensions (mm) are as shown in Table 2. This tire was mounted on a rim of size 18×7-8 and installed on the front load wheel of a 2-ton forklift.

[0111] [Table 2]

[0112] When the vehicle's running time meter showed that it had been running for 2,000 hours since the start of the test, the tire was removed from the vehicle and the appearance and structure of the tire were checked for any durability defects. No defects were found, and the Trash tire had good durability. [Explanation of symbols]

[0113] 1 Base 2 Tread section 3. Code Layer 4 Gap 32 Test Equipment 34 Test Pieces 50 Fixed part 52 Blades 54 Striking section 56 Gripping means 58 Actuator 60 Spacer 74 Back side 76 Surface 82 Arm 84 Hammer

Claims

1. A rubber composition for a base portion, comprising a diene rubber component, microfibers, and carbon black having an average particle size of 30 nm or more and 150 nm or less, the diene rubber component includes an isoprene rubber, a butadiene rubber, and a styrene-butadiene rubber; The diene rubber component contains 72 to 98 mass% of an isoprene rubber, A rubber composition in which the ratio of the maximum fiber diameter of the microfibers to the minimum fiber diameter is 1.2 or more (wherein the minimum and maximum fiber diameters of the microfibers are determined by freeze-pulverizing a sample of the rubber composition for the base portion, cutting the sample in a plane perpendicular to the extrusion direction of the rubber sheet, observing the cross section with a transmission electron microscope, and taking the maximum and minimum fiber diameters of 100 randomly selected microfibers).

2. A rubber composition for a base portion, comprising a diene rubber component, microfibers, and carbon black having an average particle diameter of 30 nm or more and 150 nm or less, the diene rubber component includes an isoprene rubber, a butadiene rubber, and a styrene-butadiene rubber; the microfiber is at least one selected from the group consisting of polyethylene terephthalate fibers, polyethylene naphthalate fibers, polyester fibers, nylon fibers, rayon fibers, cellulose-based fibers, chitin-based fibers, and chitosan-based fibers; A rubber composition in which the ratio of the maximum fiber diameter of the microfibers to the minimum fiber diameter is 1.2 or more (wherein the minimum and maximum fiber diameters of the microfibers are determined by freeze-pulverizing a sample of the rubber composition for the base portion, cutting the sample in a plane perpendicular to the extrusion direction of the rubber sheet, observing the cross section with a transmission electron microscope, and taking the maximum and minimum fiber diameters of 100 randomly selected microfibers).

3. The rubber composition according to claim 2, wherein the diene rubber component contains 72 to 98 mass % of an isoprene rubber.

4. The rubber composition according to any one of claims 1 to 3, wherein the microfibers have an average fiber diameter of 5.0 to 100 µm.

5. The rubber composition according to any one of claims 1 to 4, comprising 1 to 45 parts by mass of the microfibers per 100 parts by mass of the diene rubber component.

6. A rubber composition described in any one of claims 1 to 5, wherein the diene rubber component contains 5 to 18 mass% butadiene rubber.

7. The rubber composition according to any one of claims 1 to 6, comprising 40 parts by mass or more and 100 parts by mass or less of carbon black having an average particle size of 40 nm or more and 150 nm or less per 100 parts by mass of the diene rubber component.

8. The rubber composition according to any one of claims 1 to 7, comprising 0.1 to 20 parts by mass of a resin component per 100 parts by mass of the diene rubber component.

9. The rubber composition according to claim 1, wherein the microfibers are polyethylene terephthalate fibers.

10. A solid tire using the rubber composition according to any one of claims 1 to 9 as a base part.

11. The base portion includes two or more cord layers, 11. The solid tire according to claim 10, wherein the cord layer has at least one gap in a region near the tire equatorial plane in a tire position before being mounted on an applicable rim.

12. a ratio of a maximum width of the cord layer in the tire width direction to a rim width is 0.2 to 0.8; The ratio of the maximum tire radial height from the rim diameter line to the tire cross-sectional height is 0.05 to 0.60, 12. The solid tire according to claim 11, wherein the ratio of the minimum height in the tire radial direction from the rim diameter line to the tire section height is 0.01 to 0.

50.

13. 13. The solid tire according to claim 11, wherein the minimum width of the gap in the tire width direction is 1 mm or more and 70% or less of the maximum width of the cord layer in the tire width direction.

14. The solid tire according to any one of claims 11 to 13, wherein a ratio of a maximum width in the tire width direction of an area in which the cords of the cord layer are arranged to a maximum width in the tire width direction of the cord layer is 0.2 to 0.8.

Citation Information

Patent Citations

  • Pneumatic safety tire

    JP1982047205A

  • Pneumatic tire of bias consturction

    JP1982070705A

  • Highly rigid rubber composition

    JP1995118444A

  • Pneumatic solid tire

    JP2002144810A

  • Solid tire

    JP2002161173A